Ayat-Ayat Makkiyah Dan Madaniyah Dalam Al Quran - Milhan (Journal Smart Law, 2024)
Makkiyah and madaniyah Qur'an verses are one of the objects of study in Al-Qur'an science. Because understanding and studying the asbabun nuzul verse is very important to understand in order to know the purpose or intent of the verse revealed by Allah SWT. This study is also very influential and is a requirement to be able to become an interpreter of the Koran in order to be able to understand the context of the verses. The method used is qualitative research with a liberal research approach. Researchers conducted literature searches through various sources such as scientific journals, books, articles and other related publications. The results of the research show that there are three opinions from ulama regarding makkiyah and madaniyah, namely first, based on the place where a verse was revealed. The second is based on the exclamation or mukhotob of the verse. Third, based on the time of descent. By understanding the place or event where a verse was revealed, we can increase our belief in Allah SWT. that the Koran is the word of Allah.